Experience with Treating Lentigo Maligna with Definitive Radiotherapy - Gerald B. Fogarty; Angela Hong; Alex Economides; Pascale Guitera (Dermatology Research and Practice)
Lentigo maligna (LM) is a form of melanoma in situ that occurs on exposed, sun-damaged skin; LM can progress to invasive melanoma. Conventional surgical treatment is the preferred management option as it is usually a one-treatment episode and generates a histopathology report that records completion of excision. Some patients may not be surgical candidates due to comorbidities, patient preference, impact on function, and cosmesis or they have failed surgery with a positive margin. Other therapies, including radiotherapy (RT) and topical medicines, may then become appropriate. There is a currently accruing multi-institutional randomized trial of imiquimod versus definitive RT for this population (NCT02394132). This review is about the experience from the centre that has generated the trial and enrolled the most patients to date. The purpose of the review is to pass on experience to other centers who may want to join the trial, especially to supplement the experience of local radiation oncologists. The review covers decisions that need to be made in RT planning and treatment and how to manage side effects and other common scenarios including LM in immunosuppressed patients and in poorly vascularised tissue, after surgery, of the eyelid and of mucous membrane (mouth and nose) that are in the radiation field.